Brand Experience Melalui Fitur Keynote dalam Mempromosikan Iphone 15 - Ghina Fitriyana; Agus Hermanto (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research explores how the features of Apple's Keynote presentation influence the brand experience for the iPhone 15. The primary focus is on how the visual, narrative, and design elements in Keynote play a role in shaping consumers' sensations, feelings, thoughts, actions, and relationships with the brand. Using a qualitative approach, the study analyzes how sensory elements presented through animations and graphics enrich the consumer experience, and how touching narratives create a deep emotional connection. Additionally, the research evaluates how clear and engaging information delivery shapes consumer perceptions of the product, driving purchasing decisions and product recommendations. Interviews with key informants and consumers reveal that Keynote is effective in reinforcing brand loyalty and deepening emotional connections with consumers. A well-integrated presentation not only enhances consumer engagement but also strengthens their personal bond with the iPhone 15 brand. These findings offer valuable insights into how presentation features can be leveraged to create a positive and lasting brand experience.